2018
DOI: 10.1016/j.eurpsy.2017.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Impulsivity in early psychosis: A complex link with violent behaviour and a target for intervention

Abstract: Early intervention strategies in psychotic disorders should include evaluation of impulsivity considering it is linked to increased risk of VB and may respond to treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 49 publications
2
30
0
1
Order By: Relevance
“…It could however worsen with the emergence of psychosis, especially with the occurrence of positive symptoms. In another study we have shown indeed that the impact of impulsivity on the probability of VB was potentiated when associated with a low level of insight and a high level of positive symptoms (Moulin et al, ).…”
Section: Discussionmentioning
confidence: 87%
“…It could however worsen with the emergence of psychosis, especially with the occurrence of positive symptoms. In another study we have shown indeed that the impact of impulsivity on the probability of VB was potentiated when associated with a low level of insight and a high level of positive symptoms (Moulin et al, ).…”
Section: Discussionmentioning
confidence: 87%
“…As for other PANSS items, we selected items that were previously associated with aggression or incorporated in the same PANSS cluster as hostility: P4 excitement, G4 tension, G8 uncooperativeness and G14 poor impulse control (4,6,22,23). Excitement indicates "hyperactivity as reflected in accelerated motor behavior, heightened responsivity to stimuli, hypervigilance or excessive mood lability".…”
Section: Outcome Measuresmentioning
confidence: 99%
“…Hostile behavior can decrease the quality of life and has been associated with poorer social functioning (2). Several demographic and clinical risk factors have been reported such as male sex, socioeconomic deprivation, cannabis use, suicidality and clinical symptoms such as impulsiveness and excitement (3)(4)(5)(6)(7)(8), although there are some differences between these studies.…”
Section: Introductionmentioning
confidence: 99%
“…Analyses were conducted on 250 patients (188 NVPs and 62 VPs). The main VB characteristics (described previously [27,49]) were physical aggression, robbery with physical aggression, and assault and battery.…”
Section: Violent Behaviors During the Programmentioning
confidence: 99%